Unveiling a novel Menisporopsis species (Chaetosphaeriaceae) from Thailand - Lakshani, Pathirana S.; Bhunjun, Chitrabhanu S.; Phukhamsakda, Chayanard; Bhagya, Amuhenage T.; Maharachchikumbura, Sajeeewa S.n.; Hyde, Kevin D.; Tarafder, Entaj (Phytotaxa, 2026)
A novel species of Menisporopsis (Chaetosphaeriaceae, Sordariomycetes) was collected from Albizia lebbeck litter in Chiang Rai Province (northern Thailand) and stems of Typha angustifolia in Pran Buri Wetland (central Thailand) during a survey of aquatic and terrestrial fungi in Thailand. Multilocus phylogenetic analyses based on combined large subunit ribosomal DNA (LSU) and internal transcribed spacer (ITS) sequences placed the new isolates sister to M. theobromae and M. biformis clade. Menisporopsis amphibia is distinguishable from M. theobromae, by having subulate tips to the central setae, and conidiogenous cells with prominent periclinal thickenings that lack conspicuous dark bands at each proliferation level. Based on morpho-molecular evidence, M. amphibia is introduced as a new species, highlighting the ecological plasticity of the genus across various substrates in aquatic and terrestrial habitats. This finding contributes to the growing body of documentation on fungal diversity in the tropics.